2018
DOI: 10.1002/ajb2.1027
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental dispersal and whole‐genome duplication contribute to loss of self‐incompatibility in a polyploid complex

Abstract: When species are subject to population bottlenecks arising through multiple factors, each factor can contribute to self-incompatibility loss. In a widespread polyploid complex, the loss of self-incompatibility can be predicted by the cumulative effects of whole-genome duplication and intercontinental dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…In diploids, the haploid gametophyte expresses a single protein and is arrested if recognized by S‐RNases in the pistil; however, tetraploids will produce a mixture of homoallelic and heteroallelic gametophytes and self‐fertilization will be reduced but not eliminated. This mechanism is consistent with incompatibility breakdown in other Campanulaceae (Sutherland et al., ) and with leaky self‐incompatibility observed in J. maritima neotetraploids.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In diploids, the haploid gametophyte expresses a single protein and is arrested if recognized by S‐RNases in the pistil; however, tetraploids will produce a mixture of homoallelic and heteroallelic gametophytes and self‐fertilization will be reduced but not eliminated. This mechanism is consistent with incompatibility breakdown in other Campanulaceae (Sutherland et al., ) and with leaky self‐incompatibility observed in J. maritima neotetraploids.…”
Section: Discussionsupporting
confidence: 89%
“…Breakdown of gametophytic self‐incompatibility has been described as a direct result of genome duplications (e.g., Solanaceae, Rosaceae and other families; Lewis, ; Pandey et al., ; Entani et al., ; Adachi et al., ; Sutherland et al., ), in which pollen tubes containing two copies of the same pollen S‐allele (homoallelic) are arrested if the cognate S‐RNase is present in the pistil, while pollen grains containing two different pollen S‐alleles (heteroallelic) are compatible and thus are allowed to fertilize (de Nettancourt, ; Entani et al., ; Luu et al., ), although accumulation of non‐functional S haplotypes has also been shown (e.g., sour cherry; Hauck et al., ; Tao and Lezzoni, ). In diploids, the haploid gametophyte expresses a single protein and is arrested if recognized by S‐RNases in the pistil; however, tetraploids will produce a mixture of homoallelic and heteroallelic gametophytes and self‐fertilization will be reduced but not eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main path of polyploidization is whole-genome duplication (WGD). With the completion of a large number of plant genome sequencing projects, it has been found that WGD events have occurred in most plant evolutionary processes [21,[47][48][49]. The evolutionary process of polyploidization can be roughly divided into three stages [50].…”
Section: The Possible Mechanism Of Large Genome Size Formation In Chimentioning
confidence: 99%